Development and optimization of an HPLC–DAD method for quantification of six petroleum hydrocarbon compounds in aqueous samples. Issue 19 (13th December 2016) - Filho, Cesar M. C.; Neto, Manoel N. L.; Teixeira, Raquel S.; Pais, Alberto A. C. C.; Valente, Artur J. M.
ABSTRACT: Benzene, toluene, and xylene isomers (BTXs) and pyrene, benzo( b )fluoranthene, and benzo( a )pyrene (polycyclic aromatic hydrocarbons) are common pollutants found in many industrial effluents and in aquifers due to fossil fuels spill from underground storage reservoirs. For these reasons, the determination of these compounds has gained importance in the last decades. In this work, a simultaneous, fast, and accurate quantification of six petroleum hydrocarbon compounds (such as BTXs, pyrene, benzo( b )fluoranthene, and benzo( a )pyrene) using a high-performance liquid chromatography–diode array detector method has been demonstrated. The proposed method is suitable for the direct aqueous sample evaluation and also brings advantages, including the use of small volumes of organic solvents, with high resolution, reducing the analysis cost. The method was also checked using synthetic and real samples, including those containing surfactants, commercial gasoline, and river water samples spiked with petroleum hydrocarbon compounds. GRAPHICAL ABSTRACT: